Normative Senses of Spaces, Radical Places of Genders - Tóth, Andrea (Hungarian Journal of English and American Studies, 2020)
Book review:Kovács, Ágnes Zsófia, and László B. Sári, eds. Space, Gender, and the Gaze in Literature and Art. Newcastle upon Tyne: Cambridge Scholars, 2017. 232 pages. ISBN 9781443831550. Hb. £52.99.